Sumber Kerentanan Ekonomi Petani Kopi Di Hulu DAS Lampung: LAMPUNG SMALLHODERS COFFEE FARMER’S ECONOMICS VULNERABILITY SOURCES IN UPSTREAM WATERSHEDS - Fitriani Fitriani; Didik Kuswadi (Politeknik Negeri Lampung., 2022)
It is necessary to strengthen the resilience of farmer households by increasing their adaptability and mitigating difficult conditions or risks of business that make unsustainable. The sources of the potential economic vulnerability of farmer households are the initial information for basic dealing with business risks. The ability to identify potential sources of vulnerability as an economic risk will stimulate efforts to increase productivity, income, and rural economic growth. This research focuses on exploring the potential sources of the economic vulnerability of coffee farmers' households in the upstream Lampung watershed. The survey research conducted in coffee production centers in three sub-districts coverage​​the upstream Way Besai watershed, West Lampung. It was Air Hitam, Way Tenong, and Sumber Jaya sub-districts with a total of 165 coffee farmers as respondents. The data analysis method used a non-parametric statistical approach. The results of the study indicate that the source of the potential economic vulnerability of farmers in the upstream watershed is closely related to the ownership and area of ​​land assets. Land assets are the main source of income for farming households and a source of household expenditure allocation for both food and non-food, including for savings and investment purposes. These important factors become important entry points in efforts to build resilient farmer household resilience. Resilience is the basic social capital in achieving sustainable production.